Customer Satisfaction and Profitability: A Case of Nepalese Commercial Banks - Timalsina, Ritu (Nepalese Journal of Management, 2024)
This study examines the factors influencing profitability of Nepalese commercial banks in Kathmandu Valley. The dependent variable is profitability. The selected independent variables are reliability, responsiveness, assurance, empathy, tangibility and technology. The primary sources of data is used to assess the opinions of respondents regarding reliability, responsiveness, assurance, empathy, tangibility and technology. The study is based on primary data of 133 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of customer satisfaction and profitability: A case of Nepalese commercial banks. The study shows that reliability is positively related with profitability. It indicates that banks having reliable services towards customers leads to increase in the profitability of commercial banks. Likewise, responsiveness is positively correlated to profitability. It indicates that higher the level of responsiveness leads to increase in profitability of commercial banks. Similarly, the assurance is positively correlated to return on assets. It indicates that higher the level of assurance, higher would be the profitability of commercial banks. Further, tangibility is positively correlated to profitability indicting that better the tangibility of the banks higher would be profitability. The result also shows that technology is positively correlated to profitability. It indicates that increase in level of technological advancement leads to increment in profitability.